Analysis Of The Influence Of Price And Brand Factors On Electric Car Purchases In Semarang - Niko Darma Saputra; MY Dwi Hayu Agustini (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the influence of price and brand factors on the purchasing decisions of electric cars in Semarang City. The growing interest in environmentally friendly vehicles has not yet been followed by a high level of adoption, even though the government has provided various incentives and regulatory support. This research employs a quantitative method with purposive sampling involving 85 respondents who are electric car owners in Semarang. Data were collected through an online questionnaire and analyzed using multiple linear regression with the help of SPSS version 26. The results indicate that price and brand factors have a positive and significant effect on electric car purchasing decisions. Price contributes to shaping perceptions of value and product affordability, while brand strengthens consumer trust and loyalty through a strong image and good reputation. These findings suggest that appropriate pricing strategies and brand reinforcement are essential factors in increasing electric car purchasing decisions in Indonesia.